2008
DOI: 10.1111/j.1538-7836.2008.02890.x
|View full text |Cite
|
Sign up to set email alerts
|

Coated‐platelets in ischemic stroke: differences between lacunar and cortical stroke

Abstract: Summary. Background: Coated-platelets are a subset of platelets with procoagulant potential observed upon dual agonist stimulation with collagen and thrombin. Objective:The goal was to investigate if coated-platelet production differs between patients with lacunar ischemic stroke and non-lacunar (cortical) ischemic stroke as compared with controls. Patients and methods: Blood samples from 60 patients with ischemic stroke (20 lacunar and 40 cortical) and 70 controls were analyzed for coated-platelet production.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(84 citation statements)
references
References 24 publications
6
76
0
1
Order By: Relevance
“…1,10 The phenotypic differences between coated-and noncoated-platelets center on the presence of bound Figure 1 were subdivided according to coated-platelet levels at time of initial stroke. Recurrence incidence (%) is plotted as a function of follow-up time for lowest coated-platelet tertile group ( Á Á Á Á Á Á Á Á Á Á Á ; coated-platelet levels from 9.6% to 34.0%); middle tertile group (----; 34.1% to 46.0%); and highest tertile group ( Á -Á -Á -Á -Á ; 46.1% to 69.7%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,10 The phenotypic differences between coated-and noncoated-platelets center on the presence of bound Figure 1 were subdivided according to coated-platelet levels at time of initial stroke. Recurrence incidence (%) is plotted as a function of follow-up time for lowest coated-platelet tertile group ( Á Á Á Á Á Á Á Á Á Á Á ; coated-platelet levels from 9.6% to 34.0%); middle tertile group (----; 34.1% to 46.0%); and highest tertile group ( Á -Á -Á -Á -Á ; 46.1% to 69.7%).…”
Section: Discussionmentioning
confidence: 99%
“…The event rate estimates were based on our previously published research data on coated-platelet levels in ischemic stroke. 10,11 Sample size calculations were performed using PASS software (NCSS, LLC, Kaysville, UT, USA). 26 …”
Section: Statistical Analysesmentioning
confidence: 99%
“…32 In addition, recent studies showed abnormal coated-platelet synthesis in patients with cerebrovascular disease, with elevated coated-platelet levels in patients with nonlacunar ischemic stroke and decreased coated-platelet levels in patients with spontaneous intracerebral hemorrhage. 15,16,33,34 Finally, limited studies have indicated that coated-platelets are potentiated by inflammation. 35 Perhaps coated-platelet synthesis represents a sensitive biomarker of the disease process that includes APP abnormalities, cerebrovascular disease, and inflammatory components and may produce insight into the multifaceted pathways associated with AD.…”
Section: Discussionmentioning
confidence: 99%
“…A logical extension of our first report on coated-platelets in ischemic stroke 11 is whether these activated platelets also have a role in hemorrhagic stroke. While it is accepted that a bleeding diathesis is not the primary cause of hemorrhagic strokes, it is logical that a bleeding tendency might well contribute to the pathophysiology of this stroke subtype.…”
Section: Coated-platelets and Hemorrhagic Strokementioning
confidence: 99%